ANALISIS FINANSIAL USAHA BUDIDAYA IKAN DI DALAM KARAMBA DI DESA PULAU LANTING KECAMATAN JEMPANG KABUPATEN KUTAI BARAT KALIMANTAN TIMUR - Deddy Murwanto; Muhammad Syafril; Zul Asman Randika (Jurnal Pembangunan Perikanan dan Agribisnis, 2015)
The purposed of this research is to analyze the benefits and feasibility of financial used the investment criteria discounted such as NPV, IRR, Net B/C and Payback Period, then continued with measuring Break Event Point (BEP) period of price, product and sale. Marketing analyzing is also available of this research. The research method that used is Proportionate Stratified Random Sampling. The result of research showed that the fish cultivating business in cage generate profits for cork fish commodity snakehead Rp. 26.643.850/year, cathfish Rp. 12.260.750/year and red snakehead Rp. 12.294.800/year. Financially fish farming snakehead, cathfish and red snakhead feasible and prospective to be developed. Based on analyzing of the break even point, the actual condition of fish farming snakehead, cathfish and red snakehead in cages above the break even point of price, production and sales. There are 2 types of fish marketing, snakehead, cathfish and red snakehead, that is level two and level three.